International Financial Institutions and Their Role in Promoting the Stability of The Global Financial System - MURDIFIN, Imaduddin; HAJERING, Hajering; RAZAKOVA, Barno; SILAGADZE, Avtandil; ATANELISHVILI, Tamar (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024, 2024)
The study aims to substantiate the role of leading international financial institutions based on the analysis of their activities during the global and regional financial and economic crises. To achieve this goal, the following methods were used: comparison, generalisation, dynamic and structural analysis. The study analyses in detail the activities of international financial institutions, particularly the International Monetary Fund, the World Bank Group, and other regional financial organisations, aimed at overcoming the consequences of financial and economic crises (the Asian financial crisis of 1997-1998, the Global Financial Crisis of 2008-2009, and the COVID-19 pandemic crisis of 2020). Based on the analysis, the study summarises the main instruments, methods and approaches used by international financial institutions to promote financial stability. The study established that the main instrument is credit financing. To assess the significance of financial programmes, the amount of financial assistance was compared with the gross domestic product of individual countries that received such funding programmes. The study determined that the directions and conditions of such loan programmes differ depending on the organisation that provides them and the country that receives them. The study found that international financial institutions, particularly the IMF and World Bank Group, played a crucial role in stabilizing the global financial system during crises. The analysis of financial support, GDP growth, and inflation data highlights their impact. These findings are valuable for scholars and government officials in understanding the importance of international coordination in addressing economic crises.